Primary osteosarcoma of the breast: pathological and imaging findings - Conde,Délio Marques (2015)
SUMMARY Primary osteosarcoma of the breast (POB) is an extremely rare and aggressive tumor. Differential diagnosis of POB includes osteosarcoma of the chest wall and metaplastic breast carcinoma. Imaging tests that exclude the existence of a direct connection between the tumor and chest wall, as well as histopathological and immunohistochemical studies that rule out the presence of an epithelial component are required for the diagnosis of POB. We report a case of a 69-year old woman with POB. Imaging and pathological findings are presented. Therapeutic approach is discussed in the light of current knowledge, including potential complications.